'Beyond the facts': how a U.S. sociologist made John Stuart Mill into a 'Neo-Malthusian'. Issue 254 (22nd October 2018) - Stack, David
Abstract: This article explores the roots of the characterization of John Stuart Mill as a 'Neo-Malthusian'. Making extensive use of the Norman E. Himes Papers, held at the Countway Library of Medicine, it shows that Himes, a U.S. sociologist and committed birth control campaigner in the inter-war period, framed a characterization of Mill that endures to this day. The article demonstrates how and why Himes repeatedly took his arguments 'beyond the facts', partly in response to a dispute with the British birth control campaigner Marie Stopes, and established the practice of referring to Mill as a 'Neo-Malthusian'. The article concludes by arguing that the term impedes more than it aids our understanding and Mill scholars would benefit from stripping away decades of accreted interpretation.